First Record of Testate Amoebae on Glaciers and Description of a New Species Puytoracia jenswendti nov. sp. (Rhizaria, Euglyphida) - Santibáñez, Pamela A.; Kohshima, Shiro; Scheihing, Rodrigo A.; Silva, Ricardo; Jaramillo M, Jorge I.; Labarca P, Pedro J.; Casassa R., Gino (Acta Protozoologica, 2015)
This study documents for the first time the presence of testate amoebae on glaciers. Three shallow firn cores of 10 m depth were obtained from the Mocho-Choshuenco and Osorno volcanoes, Southern Andes, Chile, in October and November, 2005. Euglyphid testate amoebae were detected in 28 samples that correspond to the spring-summer layers of the firn cores. Inspection of 454 collected individuals reveals the presence of four different taxa. Three of these taxa, Trinema lineare, Trinema enchelys and Puytoracia bergeri have previously been reported in ice-free environments. The fourth taxon corresponds to a new species Puytoracia jenswendti nov. sp. The observation of food content and reproductive activities in a significant fraction of specimens evidence that testate amoebae are competent to inhabit glaciers. The testate amoebae found in the firn cores display clear seasonal variations in abundance indicating that these records can provide a new and novel proxy as paleoindicator for firn/ice core dating and for estimation of past glacier mass balance.